Working relations and conditions of paulista teachers (1995-2018) - Barbosa, Andreza; Jacomini, Márcia Aparecida; Fernandes, Maria José da Silva [UNESP]; Dos Santos, João Batista Silva; Do Nascimento, Ana Paula Santiago (FapUNIFESP (SciELO), 2020)
In this article, working relations and conditions of the teacher from the São Paulo state school system are analyzed, highlighting the forms of admission, career progression, base salary and working hours during the period from 1995 to 2018. The article presents a synthesis of data obtained through bibliographic research, documentary study based on national and state legislation and analysis of statistical data. It is concluded that the analyzed period was characterized by a policy of devaluation of the teaching work expressed in the large number of teachers hired on a temporary basis, in the fragile criteria of movement in the career, in the base salary below the base level of pay and in the strict noncompliance with the working hours composition expressed in the law (Lei do Piso).
Relaciones y condiciones de trabajo de los profesores paulistas (1995-2018)
Relations et conditions de travail des enseignants de são paulo (1995-2018)
Keywords: PROFESSIONAL CAREER; SALARY; TEACHING PROFESSION; WORK CONDITIONS